Voltage-tunable portable power supplies based on tailored integration of modularized silicon photovoltaics and printed bipolar lithium-ion batteries. Issue 32 (29th July 2020) - Kim, Jung-Hui; Hwang, Inchan; Kim, Se-Hee; Park, Jeonghwan; Jin, Wonjoo; Seo, Kwanyong; Lee, Sang-Young
Abstract : Voltage-tunable, all-day operating portable power supplies based on tailored integration of silicon photovoltaics and bipolar lithium-ion batteries are demonstrated with a wide voltage window, high overall efficiency, and stable cyclability. Abstract : Coupling solar cells with energy storage devices promises to overcome issues associated with intermittency and longevity of the individual systems. Despite such significance of the coupled power sources, most previous approaches have involved bulky configurations with inactive components, eventually hindering their application as portable power sources. Furthermore, to enable practical/versatile applications of the coupled power sources, their operating voltages should be widened and customized for a specific purpose. Here, we demonstrate voltage-tunable portable power supplies based on tailored integration of interdigitated-back-contact-structured crystalline-silicon photovoltaics (cSiPV) and printed bipolar quasi-solid-state lithium-ion batteries (bQSSBs). The maximum power voltages of the cSiPVs and end-of-charge voltages of the bQSSBs are respectively varied and mutually matched to widen the operating voltage window (2.7–13.5 V) of cSiPV–bQSSB. The resulting cSiPV–bQSSB achieves high overall efficiency (10.2%) and stable photo-rechargeable cyclability. Moreover, cSiPV–bQSSB featuring a customized operating voltage is seamlessly unitized with various electronic devices and exhibits sustainable long-time operation under variable weather conditions.